Bacterial secondary metabolites as promising “green” microbiologically influenced corrosion inhibitors/biocides: a review - Tkachuk, Nataliia; Zelena, Liubov (Ecological Questions, 2025)
A number of ecological, economic and medical problems arise as a result of damage to building materials by various groups of microorganisms (microbiologically influenced corrosion), as well as due to the treatment of these materials with toxic chemical biocides/inhibitors. Artificial addition of “green” biocides/inhibitors (in particular, of secondary metabolites of heterotrophic bacteria) into corrosive environments is considered as a promising approach to avoid such problems. This review is an attempt to summarize the information on the possibilities of using microbial secondary metabolites as “green” inhibitors/biocides of microbiologically influenced corrosion. The information on the anticorrosive, antimicrobial and/or antibiofilm activity of the secondary metabolites of microorganisms (antibiotics, lipopeptides, exopolysaccharides, siderophores) as well as metallic nanoparticles biosynthesized and conjugated with bacterial secondary metabolites as promising biocides/inhibitors of microbiologically influenced corrosion to protect materials from microbial deterioration, and further prospects of this approach are analyzed. It is emphasized that the inhibition of microbiologically influenced corrosion processes with the help of secondary metabolites is an environmentally safe approach that can be considered from four interrelated points of view: corrosion inhibitors, antimicrobial compounds, antibiofilm compounds, regulators of microbial corrosively active groups.